1983
DOI: 10.1073/pnas.80.23.7342
|View full text |Cite
|
Sign up to set email alerts
|

A synaptic vesicle antigen is restricted to the junctional region of the presynaptic plasma membrane.

Abstract: The plasma membrane of electric organ nerve terminals has two domains that can be distinguished by monoclonal antibodies. A library of 111 mouse monoclonal antibodies raised to nerve terminals from Torpedo californica contains 4 antibodies that bind specifically to the outside of intact synaptosomes. The distribution of the binding sites of these monoclonal antibodies on the outside of intact nerve terminals was examined by immunofluorescence and immunoelectron microscopy. The binding sites of 3 (tor23, 25, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…43). These workers hypothesized that this proteoglycan is complexed on the surface of the nerve terminal with synaptic cleft components (15). Here, we tested this hypothesis by characterizing detergent-solubilized SV2 immunoprecipitated from the surface of synaptosomes.…”
Section: Sds-page and Nitrocellulose Blotting Procedures-sds-page Wasmentioning
confidence: 98%
See 3 more Smart Citations
“…43). These workers hypothesized that this proteoglycan is complexed on the surface of the nerve terminal with synaptic cleft components (15). Here, we tested this hypothesis by characterizing detergent-solubilized SV2 immunoprecipitated from the surface of synaptosomes.…”
Section: Sds-page and Nitrocellulose Blotting Procedures-sds-page Wasmentioning
confidence: 98%
“…These are the likely locations for the attachment of the keratan sulfate side chains recognized by anti-SV1 mAb (2). Previously it was shown that the SV1 epitope of SV2 was not only present in synaptic vesicles (4) but on the nerve terminal surface of electric organ synapses as well (15). Based on this finding, Buckley et al (15) hypothesized that this synaptic vesicle proteoglycan was retained on the surface of synaptosomes due to interactions with components of the synaptic cleft.…”
Section: Sv2mentioning
confidence: 98%
See 2 more Smart Citations
“…Barat et al, 1986). Although the CNS does not contain basal laminae as such, the extracellular matrix-like material making up the synaptic cleft does contain GAGS and may provide anchorage points for the collagen-like tails of asymmetric AChE (Buckley et al, 1983). Actually, we have been able to solubilize A-forms, from chick retina, by means of heparin, with an extraction efficiency similar to that observed in "peripheral" tissues (Barat et al, 1986).…”
Section: Discussionmentioning
confidence: 78%